PERMAINAN BAHASA ATAS TUDUHAN GERAKAN FUNDAMENTALISME ISLAM DALAM POLITIK BARAT - Sulaeman, Mubaidi (IAIN Tulungagung, 2019)
The development of religious fundamentalism is inseparable from the development of political globalization which focuses on the new world order. Fundamentalism is identified with religious movements that oppose all forms of development of modernism both in part and in all aspects. This research reveals how the term 'fundamentalism' is less precise in explaining various criticisms of Islamic thought expressed in political movements against others (West). As a result, the use of the term